Sistema integrado do hospital veterinário da UFPA campus Castanhal - SOBRAL, Heitor Monteiro da Silva (2019)
The accomplishment of this monograph includes the presentation of the development process adopted to construct a proposal of software-web of use directed to the Veterinary Hospital — HV — of the Federal University of Pará — UFPA — of Castanhal. For this, adding in the application technical knowledge related to the daily life performed in the veterinary clinic. Of course, the realization of this kind of work demands the systems developer to enter into concepts that belong to another area of knowledge. With this, in a substantial way demanding the project to apply the exchange of experiences between veterinary medicine professionals and Information and Communication Technology. During the project, the absorption of such information was made possible through the skills acquired during the Bachelor’s Degree in Information Systems offered by UFPA de Castanhal. Among the capacities used, we mention: computer programming; Software Engineering"; human and computer interaction; database; among others. At the end of the work is presented as a result: the publications coming from this project; user screens developed in the system, and link access to the source code of the application built.